Evaluation of Spatial Variability of Soil and Leaf Tissue Nutrient Status and Yield (Fresh Fruit Bunch) in an Oil Palm Plantation - Syam, Tamaluddin (2002)
The study was carried out at Dusun Durian Estate, Golden Hope Plantations Berhad Banting, Selangor, in a 50 ha plot which represents a coastal oil palm plantation. The general objective of this study was to obtain accurate and timely information about the spatial distribution and status of nutrients in the soil and leaf tissue using Geographic Information System (GIS) and remote sensing technology for precision farming of oil palm plantation. Collection of soil and leaf tissue data were conducted by using systematic sampling and an Omni Star DGPS was used to precisely determine the sample sites location. Geostatistics (GS+) software and classical statistics were used for data analysis. A SPOT image of K-J.299344 acquired on March 2000 from the Malaysian Centre for Remote Sensing (MACRES) was analysed using a PCI software version 7.0. Descriptive statistical analysis classed the status of total N as low, whereas available P and exchangeable K varied from moderate to high. Soil exchangeable Ca and Mg ranged from low to moderate. Soil nutrients variability of available P, exchangeable K, Ca and Mg status were classified as high and moderate for total N. Semivariance analysis showed that the